2021
DOI: 10.7326/m20-6739
|View full text |Cite|
|
Sign up to set email alerts
|

Thrombosis, Bleeding, and the Observational Effect of Early Therapeutic Anticoagulation on Survival in Critically Ill Patients With COVID-19

Abstract: for the STOP-COVID investigators † Background: Hypercoagulability may be a key mechanism of death in patients with coronavirus disease 2019 .Objective: To evaluate the incidence of venous thromboembolism (VTE) and major bleeding in critically ill patients with COVID-19 and examine the observational effect of early therapeutic anticoagulation on survival.Design: In a multicenter cohort study of 3239 critically ill adults with COVID-19, the incidence of VTE and major bleeding within 14 days after intensive care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
141
3
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(158 citation statements)
references
References 37 publications
10
141
3
4
Order By: Relevance
“…32 Another study in critically ill patients with COVID-19 found that two-thirds of major bleeding events occurred while patients were receiving therapeutic-intensity anticoagulation. 33 Together with our 34 To minimize misclassification of bleeding events, we required documentation of bleeding in the progress notes or imaging reports and were rigorous in our adjudication of events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Another study in critically ill patients with COVID-19 found that two-thirds of major bleeding events occurred while patients were receiving therapeutic-intensity anticoagulation. 33 Together with our 34 To minimize misclassification of bleeding events, we required documentation of bleeding in the progress notes or imaging reports and were rigorous in our adjudication of events.…”
Section: Discussionmentioning
confidence: 99%
“…With the classification not remaining constant over time, it was challenging to study the effect of the intensity of anticoagulation on bleeding. The majority of previous studies on COVID-19 have not accounted for changes in anticoagulant intensity during hospital admission 14,15,33. We attempted to account for these changes by assessing anticoagulation intensity as a time-varying covariate.…”
mentioning
confidence: 99%
“…As additional data on thromboprophylaxis in COVID-19 continues to surface, international guidelines suggest a need for a risk-adapted approach to thromboprophylaxis [ 3 5 ]. Notably, while 21.0% of our study population was identified as low VTE risk, nearly half (45.5%) of patients were identified as high VTE risk.…”
Section: Discussionmentioning
confidence: 99%
“…More recent data in medical ward patients show VTE rates up to 6.2% [ 2 ], which is still substantially higher than historical rates of VTE in hospitalized non-COVID medical populations. Indeed, VTE risk in hospitalized COVID-19 patients remains a serious concern [ 2 , 3 ]. Antithrombotic guidelines recommend a universal thromboprophylaxis strategy for COVID-19 inpatients, and suggest intermediate-dose anticoagulation may be beneficial in subsets of high-risk patients [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…36 In addition, findings from two large-scale multicenter studies report lower rates of thrombotic events than initially anticipated. 12,37 Other studies have suggested that many VTE events in COVID-19 are distal deep vein thrombosis or subsegmental pulmonary embolism, 13,34 which are less likely to impact mortality. Of note, we did not notice a difference in the rate of all-cause mortality in the two study groups.…”
Section: Standard-dosementioning
confidence: 99%